Protocols for monitoring condensate formation and dynamics between the phase-separating proteins SET/TAF-Iβ and cytochrome c - Miguel Á. Casado-Combreras; Miguel A. De la Rosa; Irene Díaz-Moreno (STAR Protocols)
Summary: The targeting of several nuclear stress-response factors by translocated cytochrome c upon genotoxic stress has been demonstrated in recent years to involve liquid-liquid phase separation. This protocol addresses the need to investigate the mechanisms and features of phase separation of the histone chaperone SET/TAF-Iβ induced by cytochrome c. We provide steps for protein purification and fluorescent labeling, condensate formation, imaging, quantification, and evaluation of their dynamics by fluorescence recovery after photobleaching (FRAP). This protocol can be broadly applied to other protein complexes.For complete details on the use and execution of this protocol, please refer to Casado-Combreras et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.